Procurement of health sector goods : pharmaceuticals, vaccines, and condoms. - World Bank. (Washington, D.C. : World Bank)
Prepared by the World Bank for use by borrowers and their implementing agencies in the procurement of pharmaceuticals, vaccines, and condoms through international competitive bidding.
Issues for <2000-> have separately paged section called: Technical note, procurement of health sector goods.
At head of title: Standard bidding document.
At head of title on cover: Standard bidding document and technical note.
Description based on: May 2000.
Latest issue consulted: May 2000.
oif 19/02/15
Keywords: World Bank -- Procurement; Letting of contracts; Medical supplies industry -- Law and legislation